2007
DOI: 10.1183/09031936.00037106
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep apnoea in heart failure

Abstract: Studies from the USA have reported that sleep apnoea is common in congestive heart failure (CHF), with Cheyne-Stokes respiration (CSR) being the most frequent type of sleepdisordered breathing (SDB) in these patients. Within the present study, the authors sought to assess the prevalence and type of SDB among CHF patients in Germany.A total of 203 CHF patients participated in this prospective multicentre study. All patients were stable in New York Heart Association classes II and III and had a left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(116 citation statements)
references
References 22 publications
10
95
1
10
Order By: Relevance
“…In our cohort, 21.6% of the subjects had an AHI o15 events?h -1 , which is higher than in the general population [9], but comparable to populations with heart failure [24], arterial hypertension [28] or coronary artery disease [10], as reported previously. Our data confirm the established impact of cardiac frequency, BMI and LVM on diastolic function.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In our cohort, 21.6% of the subjects had an AHI o15 events?h -1 , which is higher than in the general population [9], but comparable to populations with heart failure [24], arterial hypertension [28] or coronary artery disease [10], as reported previously. Our data confirm the established impact of cardiac frequency, BMI and LVM on diastolic function.…”
Section: Discussionsupporting
confidence: 52%
“…Over an inclusion period of 18 months, ambulatory investigation for sleep-disordered breathing was performed with the Stardust II Sleep recorder (Philips Respironics, Best, the Netherlands), as desribed previously [24]. The median time between the echocardiographic examination and the sleep recorder study was 11.5 days (range 6-29 days).…”
Section: Polygraphymentioning
confidence: 99%
“…One such comorbidity is sleep‐disordered breathing (SDB), which is more common in HF patients than in the general population 7, 8. Data from the SchlaHF (Sleep‐Disordered Breathing in Heart Failure) registry showed that SDB in HF is highly prevalent, with nearly half of all studied patients with HF with reduced ejection fraction (HFrEF) having moderate to severe SDB, and identifying a number of risk factors for SDB in these patients, including increasing age and body mass index (BMI), decreasing left ventricular ejection fraction (LVEF), male sex, and the presence of atrial fibrillation 9…”
Section: Introductionmentioning
confidence: 99%
“…2005; Schulz et al. 2007). CHF patients with an AHI ≥10 events/h with >50% of apneas classified as obstructive were classified as having OSA.…”
Section: Methodsmentioning
confidence: 99%